Thermodynamic, structural and surface properties of rare earth metallic alloys: Au-La liquid system - Yadav, Shashit Kumar (BIBECHANA, 2023)
A complete information related to the mixing behaviours of Au alloyed with rare earth metals or lanthanides is very scarce. Therefore, an attempt has been made in this work to compute and study the temperature and concentration dependent thermodynamic, structural and surface properties of Au-La liquid alloy using different theoretical approaches. The thermodynamic properties, such as excess Gibbs free energy of mixing, enthalpy of mixing, excess entropy of mixing and activity of the system were computed using available coefficients of interaction energy parameters in the framework of Redlich-Kister polynomial. Taking these as reference values, model parameters for quasi-lattice model were optimised at 1473 K. The model parameters were then determined at higher temperatures assuming them to be linear temperature-dependent. The thermodynamic and structural properties were then computed in the temperature range 1473 K-1773 K. The surface properties of the system were computed using Bulter’s model using determined values of partial excess Gibbs free energy of its components. Present investigations revealed that the compound forming tendency of the system gradually decreased with increase in temperature of the system.